Pelaksanaan Model Pembelajaran Area di Sekolah PAUD Sejenis (SPS) Asri Wangi Desa Karangwangi Kecamatan Depok Kabupaten Cirebon - Fatimatuz Zahra (Khulasah : Islamic Studies Journal, 2020)
This research discusses the implementation of the area learning model in PAUD Asri Wangi, Karangwangi Village, Depok District, Cirebon Regency. The formulation of the problem in this research is how to implement the area learning model in PAUD Asri Wangi, Karangwangi Village, Depok District, Cirebon Regency. What factors are the obstacles in implementing the area learning model in PAUD Asri Wangi, Karangwangi Village, Depok District, Cirebon Regency. principal in developing teacher knowledge in the Area Learning Model at Rizani Putra Kindergarten. The research uses a descriptive qualitative research approach, which can provide answers to the results of the problems described. The data collection techniques used in this research are observation, interviews and documentation. The results of the research show that the implementation of the area learning model at Rizani Putra Kindergarten in the learning implementation process does not implement what has been planned by the teacher in the program design and designing the learning environment as specified in the area learning model. The obstacles faced or the factors that hinder the implementation of the area learning model in PAUD Asri Wangi, Karangwangi Village, Depok District, Cirebon Regency, are the lack of teaching staff and infrastructure, both of which are very important facilitators in the teaching and learning process. Efforts made to develop teachers' knowledge of area learning models in PAUD Asri Wangi, Karangwangi Village, Depok District, Cirebon Regency are training, workshops, seminars, and routine KKG/IGRI teacher activities once a month to increase knowledge insight. These efforts can increase knowledge and experience for teaching staff.